STREAM Education Curriculum for Primary Thai Language Teachers and School Implementation - Treekom Prommaboon; Siriluck Boongthong; Prasart Nuangchalerm (Journal of Educational Issues, 2024)
This research employed mixed method for development curriculum for primary Thai language teachers according to STREAM education. The participants were 17 volunteering primary Thai language teachers for curriculum development and 110 primary students from 6 primary schools for curriculum implementation. The findings revealed that teachers were well-versed in the STREAM education curriculum, and that instructional management was at a high level. Thai teachers were capable of developing a STREAM-based integrated curriculum and learning management system. Students can improve their reading, writing, and analytical thinking skills as a result of the implementation. The result is fruitful for teachers and students in self-development, learning skill, and learning competency by employing integrated approach. Indeed, STREAM education should be more continuously improved and invite to school curriculum and instructional practices based on different contexts.